Synthesis, Characterization and Antibacterial Studies of Some New Imidazole Derivatives - Saif M. Ali (Journal of Global Pharma Technology, 2018)
In this work, imidazole derivatives were synthesized by the reaction of benzoyl thiourea with ethyl chloro acetate (1). Hydrolysis of ester for compound (1) was synthesized by reaction of Imidazole derivative (1) with KOH give 2-((1-benzoyl-5-oxo-4,5-dihydro-1H-imidazol-2-yl)thio)acetic acid (2),compound (1)treatment with aldehydes gave ethyl 2-((1-benzoyl (Arylidene)-5-oxo-4,5-dihydro-1H-imidazol-2-yl)thio)acetate(3a-e). Hydrolysis of ester forcompound (3a-e)with KOH gives ethyl 2-((1-benzoyl (Arylidene)-5-oxo-4,5-dihydro-1H-imidazol-2-yl)thio) acetic acid (4a-e),Compound (3a-e)reaction with thiourea and HCl concentration gives ethyl 2-((9-benzoyl-6-(phenyl)-2-thioxo-2,5,6,9-tetrahydro-1H-purin-8-yl)thio)acetate (5a-e). Compound (3a-e)reaction with hydrazine hydrate gives 2-((6-benzoyl-3-(phenyl)-3a,6-dihydroimidazo[4,5-c]pyrazol-5-yl)thio)acetohydrazide (6a-e).All imidazole derivatives have been characterized by 1H-NMR, IR, and mass spectroscopy.Keywords: Imidazolederivatives, Hydrolysis, Pyrimidine, Hydrazide.